Virtual Full Duplex Wireless Networks - Zhang, Lei (ProQuest Dissertations & Theses, 2012)
A novel paradigm is proposed in this thesis for designing the physical and medium access control (MAC) layers of wireless ad hoc or peer-to-peer networks formed by half-duplex radios. A node equipped with such a radio cannot simultaneously transmit and receive useful signals at the same frequency. Unlike in conventional designs, where a node's transmission frames are scheduled away from its reception, each node transmits its signal through an assigned on-off duplex mask (or signature) over every frame interval, and receive a signal through each of its own off-slots. This is called rapid on-off-division duplex (RODD). Over the period of a single frame, every node can transmit a message to some or all of its peers, and may simultaneously receive a message from each peer. Thus RODD achieves virtual full-duplex communication using half-duplex radios without complicated scheduling at the frame level. This treatise consists of four parts, which are presented in Chapters 2–5, respectively. As a first step toward quantifying the advantage of on-off signaling, Chapter 2 studies the capacity of scalar discrete-time Gaussian channels subject to duty cycle constraint as well as average transmit power constraint. A unique discrete input distribution is shown to achieve the channel capacity. In many situations, numerically optimized on-off signaling can achieve much higher rate than Gaussian signaling over a deterministic schedule of frame transmissions. To further explore the advantages of RODD in wireless networks with half-duplex constraint, Chapter 3 evaluates the throughput of RODD, which is found to be significantly larger than that of ALOHA under some general settings. RODD is especially efficient in the case that the dominant traffic is mutual broadcast, i.e., all nodes wish to broadcast information to and receive information from their respective one-hop peers. Chapter 4 proposes a novel solution to the mutual broadcast problem in wireless networks by applying RODD signaling. Decoding can be viewed as a compressed sensing or sparse recovery problem. In the case that each message consists of a small number of bits, an iterative message-passing algorithm based on belief propagation is developed. The proposed scheme achieves several times the rate of slotted ALOHA and CSMA with the same packet error rate (1%). In Chapter 5, RODD signaling derived from Reed-Muller codes is used to carry out peer discovery in wireless networks. To identify its peers out of a large network address space, each node solves a compressed sensing problem using a chirp decoding algorithm. The algorithm is scalable to networks of virtually any size of practical interest due to its sub-linear complexity. The new scheme allows all nodes to simultaneously discover their respective one-hop peers within a single frame transmission, which entails significantly less overhead than conventional random-access discovery schemes. In summary, this thesis proposes RODD signaling, which achieves virtual full-duplex communication in wireless networks, and contributes to the understanding of its theory and applications.